2006
DOI: 10.1152/ajpheart.01120.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transient permeabilization of cell membranes by ultrasound-exposed microbubbles is related to formation of hydrogen peroxide

Abstract: In the present study, we addressed the interactions among ultrasound, microbubbles, and living cells as well as consequent arising bioeffects. We specifically investigated whether hydrogen peroxide (H(2)O(2)) is involved in transient permeabilization of cell membranes in vitro after ultrasound exposure at low diagnostic power, in the presence of stable oscillating microbubbles, by measuring the generation of H(2)O(2) and Ca(2+) influx. Ultrasound, in the absence or presence of SonoVue microbubbles, was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 25 publications
6
127
1
1
Order By: Relevance
“…Recent high-speed imaging studies have shown that microbubbles oscillating in an ultrasound field can deform cell membranes and enhance permeability (van Wamel et al 2006). Others have associated this permeability with local hydrogen peroxide formation (Juffermans et al 2006). It is possible that the sonications in our experiments produced such membrane permeabilization at the luminal surface of selected ECs, leaving the neighboring cells intact.…”
Section: Discussionmentioning
confidence: 83%
“…Recent high-speed imaging studies have shown that microbubbles oscillating in an ultrasound field can deform cell membranes and enhance permeability (van Wamel et al 2006). Others have associated this permeability with local hydrogen peroxide formation (Juffermans et al 2006). It is possible that the sonications in our experiments produced such membrane permeabilization at the luminal surface of selected ECs, leaving the neighboring cells intact.…”
Section: Discussionmentioning
confidence: 83%
“…40,44,45 More controversial is the potential role of extra and/or intracellular free radical production produced during transient cavitation. 25,46,47 We have reported that the presence of free radical scavengers in the transfection medium has no effect on transgene expression following UEGT, suggesting that free radicals are not required for sonoporation. 46 In contrast, Juffermans et al 25 found that scavenging hydrogen peroxide (H 2 O 2 ) with extracellular catalase largely prevented the increased calcium permeability induced by low MI (0.1-0.5) ultrasound (1-3.6 MHz) in H9c2 rat cardiomyoblast cells.…”
Section: Multiple Biophysical Effects Of Ultrasound May Contribute Tomentioning
confidence: 97%
“…25,46,47 We have reported that the presence of free radical scavengers in the transfection medium has no effect on transgene expression following UEGT, suggesting that free radicals are not required for sonoporation. 46 In contrast, Juffermans et al 25 found that scavenging hydrogen peroxide (H 2 O 2 ) with extracellular catalase largely prevented the increased calcium permeability induced by low MI (0.1-0.5) ultrasound (1-3.6 MHz) in H9c2 rat cardiomyoblast cells. However, these authors felt that only stable cavitation was generated in their system, despite the detection of increased intracellular H 2 O 2 -somewhat surprisingly they did not report on extracellular levels.…”
Section: Multiple Biophysical Effects Of Ultrasound May Contribute Tomentioning
confidence: 97%
See 1 more Smart Citation
“…The ultrasound irradiation can induce the apoptosis of tumor cells, including the gastric cancer cells, human leukemic cells HL-60, K562, Molt-4, U937 [3][4][5], and so on. The mechanism related to the apoptosis induced by ultrasound was suggested and three apoptotic signal processes were included.…”
Section: Introductionmentioning
confidence: 99%